Pharmacogenetics in Practice: Estimating the Clinical Actionability of Pharmacogenetic Testing in Perioperative and Ambulatory Settings. Issue 3 (12th February 2020) - Smith, D. Max; Peshkin, Beth N.; Springfield, T. Blaise; Brown, Ryan P.; Hwang, Elizabeth; Kmiecik, Susanna; Shapiro, Richard; Eldadah, Zayd; Lundergan, Conor; McAlduff, Joel; Levin, Bonnie; Swain, Sandra M.
Abstract : Most literature describing pharmacogenetic implementations are within academic medical centers and use single‐gene tests. Our objective was to describe the results and lessons learned from a multisite pharmacogenetic pilot that utilized panel‐based testing in academic and nonacademic settings. This was a retrospective analysis of 667 patients from a pilot in 4 perioperative and 5 outpatient cardiology clinics. Recommendations related to 12 genes and 65 drugs were classified as actionable or not actionable. They were ascertained from Clinical Pharmacogenetics Implementation Consortium (CPIC) guidelines and US Food and Drug Administration (FDA) labeling. Patients displayed a high prevalence of actionable results (88%, 99%) and use of medications (28%, 46%) with FDA or CPIC recommendations, respectively. Sixteen percent of patients had an actionable result for a current medication per CPIC compared with 5% per FDA labeling. A systematic approach by a health system may be beneficial given the quantity and diversity of patients affected.